Implementation and application of a stochastic aircraft boarding model. (May 2018) - Schultz, Michael
Highlights: A comprehensive and comparative overview about boarding improvements is given. The aircraft boarding model is based on a calibrated stochastic approach. Five different concepts impacting aircraft boarding time are evaluated in detail. Minor benefits are achieved by back-to-front, block strategies and hand luggage procedures. Medium benefits are achieved by outside-in boarding and infrastructural changes. Major benefits are achieved by Flying Carpet concept and individual boarding. Abstract: The aircraft turnaround processes is mainly controlled by the ground handling, airport or airline staff, except the aircraft boarding, which is driven by the passengers' experience and willingness or ability to follow the proposed boarding procedures. The paper uses a prior developed, calibrated, stochastic aircraft boarding model, which is applied to different boarding strategies (chronological order of passenger arrival, hand luggage handling), group constellations and innovative infrastructural changes (Flying Carpet, Side-Slip Seat, Foldable Passenger Seat). In this context, passenger boarding is assumed to be a stochastic, agent-based, forward-directed, one-dimensional and discrete process. The stochastic model covers individual passenger behavior as well as operational constraints and deviations. A comprehensive assessment using one model allows for efficient comparison of current research approaches and innovative operational solutions for efficient passenger boarding.